P11.52.A Peripheral neuropathies after BRAF and/or MEK inhibitors treatment: a pharmacovigilance study. (5th September 2022) - Picca, A; Birzu, C; Berzero, G; Sanchez-Pena, P; Gaboriau, L; Vidil, F; Lenglet, T; Tafani, C; Ricard, D; Psimaras, D; Bihan, K
Abstract: Background: BRAF (BRAFi) and MEK inhibitors (MEKi) demonstrated significant efficacy in the treatment of BRAF-activated tumours, firstly melanoma. Nevertheless, they are not devoid of adverse events. Sparse reports in the literature suggest the potential occurrence of peripheral neuropathies (PN) under BRAFi/MEKi treatment, but their characteristics remain poorly defined. We aimed to characterize the clinical phenotypes of PN occurring under BRAFi/MEKi treatment using a national pharmacovigilance database. Material and Methods: We queried the French pharmacovigilance database for all cases of PN toxicity attributed to at least one BRAFi or MEKi compound. Only cases with a least symptoms description and nerve conduction studies (NCS) conclusion were included. Results: Sixteen cases of PN occurred in 15 patients were identified. All patients had underlying melanoma. Two main phenotypes were seen. Six patients (dabrafenib-trametinib, n=3; vemurafenib, n=2; vemurafenib-cobimetinib, n=1) presented a length-dependent axonal polyneuropathy: symptoms were mostly sensory at lower limbs; NCS disclosed an axonal neuropathy; management and outcome were variable. Nine patients (dabrafenib-trametinib, n=5, encorafenib-binimetinib, n=3, and vemurafenib-cobimetinib, n=1) developed a demyelinating polyradiculoneuropathy: symptoms affected the four limbs and included hypoesthesia, weakness, and ataxia; cranial nerves were involved in four; NCS showed predominantly demyelinating features; most patients received intravenous immunoglobulins (n=6) or glucocorticoids (n=5), but the outcome was variable; one patient was rechallenged with a different BRAFi/MEKi with a rapid relapse. Conclusion: Patients under treatment with BRAFi/MEKi may develop treatment-induced PN. Two main phenotypes are seen: a symmetric, axonal, length-dependent polyneuropathy, and a demyelinating polyradiculoneuropathy.